The application of unmanned aerial vehicles for snow avalanche search and rescue - Albrigtsen, Andreas (UiT The Arctic University of Norway, 2016)
Snow avalanches claim in excess of 200 lives annually on a worldwide basis. However, since the invention of the first effective avalanche transceiver, the process of locating victims has remained fundamentally unchanged. Humans as a carrier for locating devices are perceived to be inefficient when moving over rugged avalanche debris, and potentially exposed to excessive risk from secondary avalanches. The technology of small unmanned aerial vehicles, also known as UAVs, are currently on the up rise as they are a low-cost, simple and effective aerial platform, which can perform a multitude of functions depending on the payload they carry. Therefore, this thesis wants to evaluate if the capabilities of UAVs could be exploited to provide valuable contributions in snow avalanche search and rescue efforts – and if so – what challenges would arise, opposing this application. Through a thorough literature review, state-of-the-art for avalanche search and rescue, UAV platforms and sensor technology is investigated to establish a theoretical frame of reference. This framework is the foundation for evaluating how to improve the current search and rescue efforts in avalanches, what capabilities current UAV and sensor technology has, and how to best apply UAVs to satisfy the needs of a rescue organization without endangering the rescuers. The subject of UAVs in search and rescue is still in its initial stages, and the amount of research and knowledge is therefore limited. Because of this the attendance of the ReCAMP workshop, Tromsø 2016, was essential with respect to the exchange of information. Tromsø Red Cross is considered pioneers on the aforementioned application of UAVs, and their collaboration was a necessity when establishing the state-of-the-art of UAV use for search and rescue purposes. The main challenges identified and discussed in this thesis is under the categories of adverse meteorological conditions and technological challenges. Weather conditions such as precipitation, extreme cold, wind and darkness are ...